Nursing students’ clinical practice education experience during the COVID-19 pandemic: a qualitative study - Soo Jin Kwon; Yoonjung Kim; Yeunhee Kwak (BMC Nursing, 2024)
Abstract Background Nursing education, including some elements of clinical practice, has largely been conducted online during the coronavirus disease 2019 (COVID-19) pandemic. Numerous studies have examined the experiences of nursing students in academia during the pandemic. However, research on nursing students’ clinical practice experiences is limited. This study aimed to analyze nursing students’ clinical practice experiences during the COVID-19 pandemic. Methods This study used a qualitative research design and performed thematic analysis. Participants comprised 13 nursing university students with clinical practice experience at a hospital during the COVID-19 pandemic. Interviews were conducted either online or face-to-face. Data were collected during June‒July 2021. Results Four themes and eight subthemes were generated through thematic analysis. Theme 1 was “Nursing students’ anxiety and strict adherence to quarantine practices,” with the subthemes of “Fear of infection” and “Protecting themselves.” Theme 2 was “Nursing students’ belief that their organization is protecting them,” with the subthemes of “Strict quarantine rules at hospitals and universities” and “The nursing students regretted the limited scope of practice but felt safe.” Theme 3 was “Learning through valuable practice,” with the subthemes of “Recognizing the importance of practice” and “Realizing the benefits of practice.” Theme 4 was “A sense of duty as a prospective nurse,” with the subthemes of “Accepting a sense of duty as a nurse” and “Establishing the expanded role of a nurse.” Conclusions The nursing students recognized the importance of nursing practice during the pandemic and worked harder. A better understanding of the experiences of nursing university students who completed their clinical practice during the COVID-19 pandemic can help nursing professors and managers more effectively train students during times of high stress.